Determining the potential of gastronomy tourism development in Vietnam through the dynamic capabilities lens - Alonso, Abel Duarte (2025)
The purpose of this research was to examine Vietnam’s gastronomic resources as development tools to become a gastronomy tourism destination. Integrating the underpinnings of the dynamic capabilities approach, which predicates sensing opportunities, seizing them and reconfiguring, the study gathered the experiences of 35 executive chefs through semi-structured open-ended interviews. The ensuing analysis generated 12 dimensions and a conceptual framework. For instance, sensing is symbolised by internal, external, chef, and industry-related triggers, emphasising the nation’s gastronomic traditions, its growing international recognition, and chefs’ trailblazing role. The ‘enticing palates’ and ‘pre-empting potential’ dimensions are key seizing representations, the first underlying the distinctiveness of Vietnamese gastronomy and the second its extensive repertoire. Finally, reconfiguring is reflected by ‘banking on uniqueness’, which stresses maintaining a gastronomic identity while ‘championing the home-grown’ the involvement of gastronomy ‘gatekeepers’. The resultant framework provides an in-depth guide, enhancing the practical and conceptual understanding of gastronomy tourism’s development.